COMPARISON OF GOTHIC SETTING IN TELEVISION SERIES WEDNESDAY (2022) AND THE CHILLING ADVENTURES OF SABRINA (2018) - Khairunnisa, Syifa Aulia (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This research’s objective is to find the comparison of two television series, Wednesday (2022) and The Chilling Adventures of Sabrina (2018) of their setting in Gothic element using the theory of Fred Botting. Based on Botting’s theory, the setting in Gothic fiction was divided into two types, natural sublime and synthetic sublime. This research answered the question of what Gothic’s setting in the television series Wednesday (2022) and The Chilling Adventure of Sabrina (2018) and the comparison between the two television series regarding the Gothic’s setting. This research’s objective requires a deep understanding of the topic, so the qualitative descriptive method is applied in this research. Based on this reseach, it was found that there are nine Gothic setting in Wednesday (2022) and six in The Chilling Adventures of Sabrina (2018).  On that note, four similarities and seven differences was also found regarding the Gothic setting between the two television series. Based on the analysis, Wednesday (2022) has more Gothic setting compared to The Chilling Adventures of Sabrina (2018) both in natural and synthetic sublime, with with one more data on natural sublime and four more data on synthetic sublime.